PREFERENSI PEMILIH MUSLIMS DALAM PEMILIHAN KEPALA DAERAH SERENTAK 2020 DI SUMATERA BARAT DAN SULAWESI UTARA - Delmus Salim (Politea : Jurnal Politik Islam, 2022)
This article focuses on the influence of religious sentiment in the simultaneous regional head elections in West Sumatra and North Sulawesi in 2020. This article discusses political behavior that is influenced by the religion of voters in provinces with a Muslim majority and minority. Data collection was carried out by survey using interviews and online applications with Muslim voters on the reasons that influenced them in choosing regional heads. This study reveals that religious sentiments have a strong influence on Muslim political behavior in West Sumatra and not in North Sulawesi. This Muslim political behavior is related to the history of colonialism in Indonesia and the management of religious resources in the two areas studied. Regional heads in Muslim-majority and minority areas greatly influence the dynamics of religious resources in the areas they lead. This study, in turn, highlights the importance of developing strategies for managing religious resources in Indonesia.